Agent-based modelling and simulation of task execution and coordination in distributed organisations: the psychosocial dynamic interaction perspective. (2018) - Liu, Haibin; Cheng, Yufang; Bo, Qinghe
The research presents a psychosocial dynamic model of members' commitment to perform local tasks and global tasks under a distributed context. Based on theory of planned behaviour, we explore how local task self-efficacy and IT self-efficacy evolve with a computational model. The simulation results of the aerospace industry show that the organisation will emerge to a non-balanced state of development. Moreover, sites which form the distributed organisation will evolve to the independent locations in the end. For overcoming these situations, the study proposes a strategy - 'resisting foreign aggression home safe'. Moreover, a high rate of global tasks accomplishment can be achieved by improving members' IT self-efficacy, which brings in more communication and coordination between separated sites. For distributed organisations, the higher and the lower coordination are not rewarding, while the high local task self-efficacy and the moderate IT self-efficacy are beneficial.